1985
DOI: 10.1002/jcp.1041220221
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive regulatory control of system a transport activity in a kidney epithelial cell line (MDCK) and in a transformed variant (MDCK‐T1)

Abstract: Adaptive regulatory control of System A activity was investigated using MDCK cells and a chemically induced, oncogenic transformant of MDCK cells, MDCK-T1. Within 7 hours after transfer to an amino-acid-deficient medium, A activity of subconfluent MDCK cells had maximally derepressed, but this activity in confluent MDCK cells and in subconfluent transformed cells showed little capacity for derepression. Amino-acid-starved, subconfluent MDCK cells were used to study trans-inhibition and repression of A activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

1985
1985
2000
2000

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 36 publications
0
29
0
Order By: Relevance
“…In addition, we observed the appearance of a second low affinity system A transport component not observed in control animals. This dichotomy in system A-mediated transport has been observed by others (28,29), particularly under conditions derepressing system A, such as amino acid starvation and cellular transformation (28). Such a TNF-induced heterogeneity in system A transport may translate into an additional augmentation of hepatic amino acid uptake in vivo during sepsis.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In addition, we observed the appearance of a second low affinity system A transport component not observed in control animals. This dichotomy in system A-mediated transport has been observed by others (28,29), particularly under conditions derepressing system A, such as amino acid starvation and cellular transformation (28). Such a TNF-induced heterogeneity in system A transport may translate into an additional augmentation of hepatic amino acid uptake in vivo during sepsis.…”
Section: Discussionmentioning
confidence: 60%
“…6 B). The observed increase in uptake was due to a fourfold increase in the maximal velocity (28,29). Similarly, Na'-dependent glutamine transport was increased in vesicles from TNFtreated rats across all assay glutamine concentrations (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Both phases are referred to as adaptive regulatory control and are protein synthesis dependent, a feature which distinguishes adaptive control from transinhibition. System A activity of chemically transformed MDCK-T1 118 BOERNER AND SAIER cells was severalfold higher than observed with MDCK cells (Boerner and Saier, 1982a1, showed no capacity for derepression, was resistant to repression (i.e., irreversible inactivation) by amino acids, and retained sensitivity to transinhibition (Boerner and Saier, 1985a). Kinetic analyses indicated that MeAIB uptake by MDCK-TI cells, measured as a function of MeAIB concentration, exhibited biphasic kinetics, a feature similar to that observed with amino-acid-starved but not amino-acidfed MDCK cells (Boerner and Saier, 1985a).…”
mentioning
confidence: 77%
“…Differentiated characteristics are often expressed as a result of cell-cell communication (Lever, 1985;Pfaller et al, 1990). The MDCK and LLC-PK1 cells are heterogeneous populations (Boerner and Saier, 1985;Lever, 1985;Wohlwend et al, 1986;Gstraunthaler and Handler, 1987), which could increase their ability to express differentiated characteristics. The ST-li and STt-4i cells were derived from clonal populations and have been surrounded by the same kidney cell type throughout their in vitro culture history.…”
Section: Sample Collection and Assay Of Enzyme Activitiesmentioning
confidence: 99%